PEMBELAJARAN COOPERATIVE LEARNING METODE CASE STUDIES DENGAN MEDIA KOMIK PADA MATA PELAJARAN EKONOMI DI SMA MUHAMMADIYAH 3 BANCAR - Risa Mahmudah; Candra Aeni; Ridaul Innayah (FKIP Unirow Tuban, 2017)
The problem in this research is the low of student learning activity in economic learning process, Thus causing student learning outcomes that have not been optimal. The purpose of this study is to describe the activity of teachers in implementing cooperative learning with cases study method with comic media, describing the activities of students in following the learning process using cooperative learning with cases study method with comic media, And describe student learning outcomes after applied cooperative learning with cases study method with comic media. Cooperative learning model of case study method with comercial media is learning which emphasizes on heterogeneity and cooperation among students. Students are given the opportunity to interact and work together by doing tasks in groups and then exchanging group members with other group members and returning to early group members in a pleasant atmosphere. This research was conducted in SMA Muhammadiyah 3 Bancar. The subjects of this research is students of class X of the academic year 2016/2017, which amounted to 29 students, and who acted as observer in this reseacrh is Economics subject teachers and students of the education program of Economics class of 2013. Result of this research that the activity of teachers experienced an increase in the first cycle is 62.5%, the second cycle is 72.5%, and the third cycle is 88.75%. Student activity has increased that is in cycle I is 45,64%, cycle II equal to 63,7%, and cycle III equal to 83,36%. Student learning outcomes also experienced an increase that is in the first cycle of 41.37%, the second cycle of 58.62%, the third cycle of 79.31%. Based on the results of this study, it can be concluded that the implementation of learning cooperative learning method of case studies with comic media can increase the activity and learning outcomes of Economics subjects in the class X students in SMA Muhammadiyah 3 Bancar 2016/2017 academic year.